DNA double-strand breaks in telophase lead to coalescence between segregated sister chromatid loci - Ayra-Plasencia, Jessel (Nat Commun, 2019)
DNA double strand breaks (DSBs) pose a high risk for genome integrity. Cells repair DSBs through homologous recombination (HR) when a sister chromatid is available. HR is upregulated by the cycling dependent kinase (CDK) despite the paradox of telophase, where CDK is high but a sister chromatid is not nearby. Here we study in the budding yeast the response to DSBs in telophase, and find they activate the DNA damage checkpoint (DDC), leading to a telophase-to-G(1) delay. Outstandingly, we observe a partial reversion of sister chromatid segregation, which includes approximation of segregated material, de novo formation of anaphase bridges, and coalescence between sister loci. We finally show that DSBs promote a massive change in the dynamics of telophase microtubules (MTs), together with dephosphorylation and relocalization of kinesin-5 Cin8. We propose that chromosome segregation is not irreversible and that DSB repair using the sister chromatid is possible in telophase.